Augmented Reality in Business Marketing. A Systematic Review of Literature from 2016 – 2021 - Luis A. PAREDES ALMONACID; Anthony J. CISNEROS HARO; Liset S. RODRIGUEZ BACA (Communications of International Proceedings, 2021)
Technology in today's world has been constantly developing and even every different day a replacement technology is presented to people. They are largely new tools. Augmented reality is one of these technological advances, which will benefit in many areas [1]. That is why the importance of augmented reality in business marketing is carried out. This research is based on understanding articles published between the years 2016 to 2021, which were extracted from 5 databases such as EbscoHost, IEEE Xplore, IOPScience, ScienceDirect and Scopus. Obtaining a total of 55 articles of reliable investigation, related to the studied topic. The result of the research shows the value of the subject studied, the year and the continents that contributed the most to this study.
Keywords: Augmented Reality; Technology; Business Marketing.